Seaports in the BRI: Challenges, Solutions and Emerging Regulations - Vitali Serafimov; Oleg Stets; Andriy Shkolyk (Lex Portus, 2021)
The article examines ways to increase the efficiency of seaport projects within the framework of the Belt and Road Initiative. It considers the new challenges and threats posed by the COVID-19 pandemic and the crisis in the maritime sphere. The first direction of the research was an analysis of the current stage of the implementation of the BRI in the global port industry, attempts to strengthen the influence of the People’s Republic of China (the PRC) on the national port facilities and the reasons for the wrecking of the large, planned projects. The authors note the “rigidity” of China’s “soft power” in promoting and consolidating influence on the maritime port industry. The second part of the article describes the modern practice of implementing the BRI in Europe. The positive and negative aspects of cooperation of the People’s Republic of China with the EU countries are considered. The focus is on the strengthening influence of regionalism in the European port policy under conditions of the COVID-19 pandemic. In addition, the authors point out a natural gradual “cooling” of attitude towards the Chinese investment projects in connection with the focus on strategic sectors of the economy of the EU member states, reinforced by the spread of the pandemic. Based on the analysis, the ways to increase confidence in Chinese investment in the European region are proposed. The third direction of the analysis is the growth of the BRI northern segment, the beginning of the formation of the Ice Silk Road, and the investment projects of the PRC in the seaports of the traditional near-arctic states.